2013
DOI: 10.3171/2013.8.jns121854
|View full text |Cite
|
Sign up to set email alerts
|

Selective amygdalohippocampectomy versus anterior temporal lobectomy in the management of mesial temporal lobe epilepsy: a meta-analysis of comparative studies

Abstract: Object. Whether selective amygdalohippocampectomy (SelAH) has similar seizure outcomes and better neuropsychological outcomes compared with anterior temporal lobectomy (ATL) is a matter of debate. The aim of this study was to compare the 2 types of surgery with respect to seizure outcomes and changes in IQ scores.Methods. PubMed, Embase, and the Cochrane Library were searched for relevant studies published between January 1990 and September 2012. Studies comparing SelAH and ATL with respect to seizure and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
2
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(98 citation statements)
references
References 39 publications
2
88
2
6
Order By: Relevance
“…Nonetheless, three studies have found better seizure-control in patients submitted to ATL 4,22,23 . Similarly, two recent systematic reviews concluded that ATL is associated with a reduced rate of seizure recurrence compared to SelAH 24,25 . In other words, a consensus on this matter has not yet been reached.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, three studies have found better seizure-control in patients submitted to ATL 4,22,23 . Similarly, two recent systematic reviews concluded that ATL is associated with a reduced rate of seizure recurrence compared to SelAH 24,25 . In other words, a consensus on this matter has not yet been reached.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies concluded that there are no differences between the two approaches, including the systematic review conducted by Hu et al 16,25,26 . Nevertheless, many other studies claim that SelAH confers lower cognitive morbidity, mostly involving language and verbal memory.…”
Section: Discussionmentioning
confidence: 99%
“…Two large meta-analyses of studies comparing the two procedures head to head found higher rates of seizure freedom after ATL than after SAH (52,53). One study found no significant difference in intelligence quotient scores between patients receiving the two procedures, and one was unable to make significant conclusions regarding differences in neuropsychiatric outcomes between the two groups.…”
Section: Selective Amygdalohippocampectomy (Sah)mentioning
confidence: 99%
“…A maior parte das discussões relativa aos acessos cirúrgicos ao CTVL é centrada no tratamento cirúrgico da esclerose hipocampal, a forma mais comum de epilepsia resistente ao uso de medicações observada nos centros de cirurgia de epilepsia, respondendo por 17% a 31% dos procedimentos cirúrgicos realizados para o tratamento de epilepsia (Pasquier et al,2002;Piao et al, 2010, Hu et al,2013.…”
Section: Considerações Sobre Os Acessos Cirúrgicos Ao Corno Temporal unclassified
“…2005;Hu et al,2013), as controvérsias tem se concentrado na necessidade de se incisar, ressecar ou retrair o lobo temporal durante os procedimentos cirúrgicos (Penfield, 1954;Falconer;Wilson, 1958;Niemeyer, 1958;Marino;Rasmussen, 1968;Niemeyer;Bello, 1973;Weiser;Yasargil, 1982;Spencer et al,1984;Yasargil et al, 1985;Pasquier et al,2002;Piao et al, 2010;Hu et al,2013). Tais controvérsias tem norteado o desenvolvimento de acessos cirúrgicos não só para o tratamento das crises epilépticas, mas também para as lesões neoplásicas (Yasargil, 1994(Yasargil, , 1996(Yasargil, , 2005Yasargil et al, , 2010Smith et al, 1995;Ture et al, 2004Ture et al, , 2012de Oliveira et al, 2012) e vasculares (Heros, 1982;Ikeda et al, 2002;Yasargil, 1994Yasargil, , 1996Yasargil, , 2005Yasargil et al, , 2010Abla et al,2011;Ture et al;de Oliveira et al, 2012) que podem incidir nesta região.…”
Section: Considerações Sobre Os Acessos Cirúrgicos Ao Corno Temporal unclassified